Room-temperature direct bonding of germanium wafers by surface-activated bonding method. (22nd January 2015) - Higurashi, Eiji; Sasaki, Yuta; Kurayama, Ryuji; Suga, Tadatomo; Doi, Yasuo; Sawayama, Yoshihiro; Hosako, Iwao
Abstract: This paper reports the mechanical and electrical characteristics of Ge/Ge interfaces prepared by room-temperature surface-activated bonding (SAB). Bonded Ge/Ge wafer pairs with high bonding strength equivalent to that of the bulk material were achieved without any heat treatment. It was found that the bonding of Ge wafers was not sensitive to the background vacuum pressure in a wafer-bonding chamber compared with the bonding of Si wafers. The current–voltage characteristics and microstructures of bonded interfaces formed by SAB and low-temperature plasma activation bonding (PAB) were compared. It was demonstrated that junctions with very low resistivity can be obtained by SAB at room temperature.